2020
DOI: 10.3390/su12166407
|View full text |Cite
|
Sign up to set email alerts
|

Scripting, Situating, and Supervising: The Role of Artefacts in Collaborative Practices

Abstract: While calls for cross-sectoral collaboration have become a recurrent motif in sustainability-oriented policymaking and research, the practical realization of such processes presents significant challenges. The hope for “collaborative advantage” often gets traded for the experience of “collaborative impasse”, namely those moments in which collaboration gets stuck. To better understand the reasons underlying such impasses, the study focuses on the impact of facilitation artefacts—objects designed and used in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…SO-type processes can work; this way, deliberation can occur with fewer resources, but it is vulnerable to domination and not particularly satisfying as regards output and, possibly, learning. By using artifacts like response templates or detailed instructions, some benefits of facilitation might be able to be realized without the presence of a facilitator (Molinengo and Stasiak 2020). Facilitation designs like the MM process can bring people together and motivate them; this can be helpful when working together is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SO-type processes can work; this way, deliberation can occur with fewer resources, but it is vulnerable to domination and not particularly satisfying as regards output and, possibly, learning. By using artifacts like response templates or detailed instructions, some benefits of facilitation might be able to be realized without the presence of a facilitator (Molinengo and Stasiak 2020). Facilitation designs like the MM process can bring people together and motivate them; this can be helpful when working together is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Asenbaum (2016) examines the characteristics of one particular facilitation method, dynamic facilitation, documenting how these facilitators address exclusionary tendencies and enable diversity while steering toward consensus. Molinengo and Stasiak (2020) argue that for facilitation, the planned interaction modes and material ' artefacts' used by facilitators can play a significant role in achieving (or impairing) collaborative advantage. As regards online deliberation, Trénel (2009) found that higher quality facilitation could minimize the effects of internal exclusion.…”
Section: The Importance Of Facilitation For Deliberative Mini-publicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More conventional set‐ups that make use of stages and podiums create a physical separation between participants that reinforce hierarchies and hampers engagement. Removing physical barriers can help to create an atmosphere that is less competitive and in which all participants can contribute as experts of equal standing (Molinengo & Stasiak, 2020).…”
Section: Toward Developing a New Communication Culture At The Copmentioning
confidence: 99%